Herpes zoster: Epidemiological Features of the Incidence in 2019 - A. N. Kaira; V. F. Lavrov (Эпидемиология и вакцинопрофилактика, 2020)
The urgency of the problem of herpes zoster (shingles) consists in its wide distribution in the world, high incidence rates in a significant part of the subjects of the Russian Federation, as well as the severity of complications caused by this infection.The aim of the study was to analyze the epidemiological characteristics of the incidence of herpes zoster in Russia.Materials and methods. Epidemiological analysis of the incidence of herpes zoster in the Russian Federation was conducted using official statistics.Results and discussion. In 2019, in a number of administrative divisions of the Russian Federation, there was a poor epidemic situation associated with the incidence of herpes zoster. In some regions, the incidence rates were significantly higher than the national average, and the elderly were the most vulnerable. It turned out that the existing methods of prevention of herpes zoster, aimed mainly at promoting a healthy lifestyle and hygienic education of the population, do not bring the desired results, and the incidence of herpes zoster (secondary VZV infection) remains high.Conclusions. The analysis of the incidence of herpes zoster during the reporting period demonstrates the need for constant statistical accounting of the spread of this infection on the territory of Russia, actualizes the conduct of full-fledged epidemiological surveillance and the organization of a system of preventive measures, which should be based on the development, production and practical application of a domestic vaccine against herpes zoster.